Development of Foreign Material Detection in Food Sensor Using Electrical Resistance Technique - Rizalman, N. F. I. S.; Rashid, W. N. A.; Lokmanulhakim, N.; Elmy Johana Mohamad (International Journal of Integrated Engineering, 2019)
Food inspection has been a serious matter in the food industry as the contamination by foreign materials such as metals, bone, plastics and glass in food plays a major impact on the industry. In spite of a great deal of effort to prevent mixing foreign bodies in food materials, food manufacturers have still not been able to detect them. Electrical Resistance Sensor to detect the foreign material in food detection sensor is constructed and presented in this work. This project focuses on how to design and implement the system to detect and distinguish between food and foreign material using resistance concept. The electrode plate of Electrical Resistance Sensor (ERS) is designed using COMSOL Multiphysics Software to see the electric field and contour of the electric potential of the system. The resistance value from the sensor is measured based on the AC Circuit concept. The alternating current from the sensor flows to the charge detector circuit providing the voltage corresponding to the resistance between the electrode pair. The voltage from the charge detector circuit has been amplified by the amplifier circuit to obtained DC output from an AC input signal. The voltage form circuit has been converted from the analog to digital signal using Bluetooth Electronics Application via Arduino Uno through HC-05 Bluetooth module. The Bluetooth Electronics Application is used as a graphical user interface (GUI) to display the condition of the material tested including food and foreign material to a smartphone. The experiment results show that the electrical resistance sensor are able to detect the foreign material in food by changes of the resistance value. If the food was detected with the foreign material (non-conductive), the value of resistance will decrease due to the flow of electric current.